2004
DOI: 10.1097/01.aog.0000113623.18286.20
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in the Incidence of Gestational Diabetes Mellitus: Northern California, 1991–2000

Abstract: II-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
303
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 388 publications
(330 citation statements)
references
References 23 publications
15
303
4
8
Order By: Relevance
“…International population studies have also shown trends of increases in the presence of diabetes in pregnancy. 2,7,8,11 These findings reinforce the theory that the increase in diabetes described in the population of Ribeirao Preto 14 may also be observed in the presence of DM in women resident in the city giving birth.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…International population studies have also shown trends of increases in the presence of diabetes in pregnancy. 2,7,8,11 These findings reinforce the theory that the increase in diabetes described in the population of Ribeirao Preto 14 may also be observed in the presence of DM in women resident in the city giving birth.…”
Section: Discussionsupporting
confidence: 77%
“…Various studies report the growing trend of gestational and pre-gestational diabetes mellitus (GDM), 7,8,11 which is linked to higher risk of morbidity and maternal and perinatal mortality. 2,6,18,21 In the USA, the growing trend for the presence of GDM in hospital deliveries, in all age groups has been described for the period 1994-2004, with a marked increase in type 2 diabetes.…”
mentioning
confidence: 99%
“…We searched the KP hospital discharge and billing claim databases to identify all singleton live births, and searched the KP laboratory database to obtain all plasma glucose values measured during screening glucose challenge tests (GCTs) and diagnostic 3-h OGTTs [13]. We restricted our cohort to women who delivered between 1 January 1996 and 31 June 1998, because the recommendations from the 4th International Workshop Conference on GDM [8] were published in August 1998.…”
Section: Methodsmentioning
confidence: 99%
“…GDM is a common pregnancy complication affecting 2-10% of the pregnancies in the United States (2). In general, Asian women compared with other racial/ethnic groups in the United States have a higher risk for GDM (3)(4)(5)(6). In urban China, the prevalence of GDM has increased from 2.4% in 1999 to 8.2% in 2012 (7) using the WHO's criteria (8).…”
Section: Introductionmentioning
confidence: 99%